Mouth- Soluble Innovations: The Rise of Oral Dispersible Films in Modern Pharmacotherapy - Bala, Anju; Verma, Inderjeet; Dora, Chander Parkash (Journal of Neonatal Surgery, 2025)
Oral thin film is a drug delivery platform that has been demonstrated to be a method of administration that is acceptable to all age groups. The genesis of oral strip formulation began with the necessity to develop a dosage form that could be easily administered to patients suffering from dysphagia. Orally dispersible films are mainly preferred for elderly, pediatric, psychiatric, paralyzed, and mentally disordered patients. They are polymeric matrices that provide a controlled drug release to target sensitive spots, which is impossible to do with pills or liquid formulations. An oral thin film is a flexible, ultra-thin film containing an active substance that dissolves or disintegrates in the saliva at an incredibly fast rate, in a matter of seconds, without the use of water or chewing. The development of oral thin film products started with nonmedicinal products. Pfizer's first non-medicinal product was Listerine® PocketPacksTM strips, which were used as a mouth freshener. Film-forming polymers, organoleptic compounds, plasticizers, saliva-stimulating agents, thickeners, and stabilizers are utilized in the formulation of oral thin films. The surface area of fast-dissolving films typically ranges from 5 to 20 cm2, and the drug is inserted in matrix form using a hydrophilic polymer. Since high-dose medications are challenging to combine into thin films and the film only comprises 5–30% w/w of the drug, low-dose pharmaceuticals were used. Solvent casting methods are mainly used for the manufacturing of oral thin film. Concepts and evolution, over-the-counter and prescription products, some patent technology, and previous work done by different researchers on oral thin film are discussed in this review. Finally, the review concludes by giving an overview of the ODF of herbal extract, patent, and clinical trials on the development of oral thin film.